Paving the Walkway Towards the Newly Constructed Toilet at The Faculty of Engineering, Technology, Applied Design and Fine Art. - Aganyira, Allan (Kabale University, 2023)
This report contains all the activities carried out during the execution of this project. That is paving the walkway. The activities include research making, literature review, methodologies used and outcomes future prospects and recommendations. There is moulding of paver blocks, process, and materials used, and curing.